ANALYSIS AFFIXATION USAGE ON SONGS LYRICS OF HANDWRITEN ALBUM BY SHAWN MENDES - Ni Luh Ruska Antarika; Ni Putu Astiti Pratiwi (Sekolah Tinggi Pariwisata Mataram, 2021)
The purpose of this research is to determine the affixation in The Script song lyrics. The primary goal of this research is to determine how the affixation process occurs in the lyric